Polymer based composites with interpenetrating networks structure - Steller, Ryszard; Kedziora, Grazyna; Trojanowska-Tomczak, Monika; Ciesla, Katarzyna; Skorupski, Jakub (Publishing House of Lviv Polytechnic National University, 2013)
Preparation and properties of composites consisting of two continuous interpenetrating phases,at least one of them is the polymer phase, are presented. Three different kinds of such composites are discussed: polymer-polymer (PVC-PMMA), polymer-mineral (PMMA-gypsum) and polymer-metal (PVC-Wood alloy). Composites were prepared by filling the porous matrix made of one component with other component in the liquid state which was then solidified by polymerization (PMMA) or cooling (Wood alloy).The obtained composites were characterized mainly by mechanical testing,e.g. elasticity modulus, flexural strength and Brinell hardness. In some cases other measurements, such as microscopic and electrical, were also carried out. It was found that obtained composites possess many interesting properties. The introduction of the second component into the matrix pores as a rule increases the mechanical properties by few times, even if its content is relatively small. Вивчено одержання і властивості композитів, що складаються з двох суцільних взаємопроникних фаз, одна з яких принаймні, є полімерною. Розглянуто три різних види таких композитів: полімер-полімерні (ПВХ- ПMMA), полімер-мінеральні (ПMMA-гіпс) і полімер-металеві (ПВХ-сплав Вуда). Приготування композитів відбувалось заповненням пористої матриці одного компонента іншим компонентом в рідкому стані, яку потім затверджували внаслідок полімеризації (ПММА) або охолодженням (сплав Вуда). Визначено характеристики отриманих композитів:модуль пружності, міцність на вигин і твердість за Брінеллем та деякі мікроскопічні та електричні вимірювання. Встановлено, що отримані композити характеризуються оригінальними властивостями. Показано, що введення другого компонента, навіть при малому його вмісті, в пори матриці,підвищує в декілька разів механічні властивості виробу.
Полімерні композити із взаємопроникною структурою
Keywords: composite; poly(methyl methacrylate); poly(vinyl chloride); mechanical properties; композит; поліметилметакрилат; полівінілхлорид; механічні властивості